Improving the efficiency of drying Eisenia Fetida by using a technique with induced heat and mass transfer - Pogozhikh, Nikolay; Pak, Andrey; Pak, Alina; Sychov, Andrii; Sychova, Tatiana; Sofronova, Maryna (Eastern-European Journal of Enterprise Technologies, 2022)
This paper substantiates the need to rationalize the drying process of such a vermitechnology object as Eisenia Fetida worms to utilize them as feed for industrial animal husbandry and poultry farming. This will contribute to improving the energy efficiency of vermitechnology application in the production of agricultural products. A technique of drying with the effect of induced heat and mass transfer has been adapted for raw materials with a low amount of dry substances, which is a homogenate of worms. Two adaptation techniques are proposed: drying the homogenate in a heat and mass exchange module with artificially created obturators; drying a mixture of homogenate with grain bran with the spontaneous formation of obturators from raw materials. Studies of various homogenate drying techniques have established that the longest duration of dehydration is achieved by convective drying technique. This is 1.2 times larger compared to the conductive technique and 2 and 3 times larger than drying with the effect of induced heat and mass transfer depending on the technique of obturator formation. It has been established that the final moisture content of dried products is the smallest for techniques involving the effect of induced heat and mass transfer. It is in 2...3 times less compared to convective and conductive techniques. Drying with the effect of induced heat and mass transfer of mixtures with the following mass ratio of the homogenate to grain bran was investigated: 1:1; 2:1; 3:1. It was established that for a sample with a ratio of 3:1, the nature of the kinetics of drying is different from the typical kinetics for the effect of induced heat and mass transfer. The consequence is an increase in the duration of dehydration compared to samples of 1:1 and 2:1 by 1.3 times. The results can be used in agriculture, namely, industrial animal husbandry, poultry farming, and vermitechnology